Kinerja Pegawai Rumah Sakit : Peran Lingkungan Kerja, Kepuasan Kerja, Dan Motivasi Kerja - Zulkifli, Dafa Labiq; Bagis, Fatmah; Astuti, Herni Justiana; Suyoto, Suyoto (JURNAL ILMIAH EDUNOMIKA, 2024)
This research aims to determine the influence of the work environment, job satisfaction, work motivation and performance of hospital employees involving all hospital staff. Through the application of non-probability techniques, especially the purposive sampling method, a research sample of 142 respondents was obtained who met certain criteria. The data collection process requires distributing questionnaires. The purposive sampling method was deliberately used to ensure participants met the predetermined criteria. Analysis of the collected data uses Partial Least Square (PLS) analysis. The results of the analysis show that the work environment has a significant and positive effect on employee performance. Additionally, job satisfaction was determined to have a noteworthy positive influence on employee performance. Apart from that, work motivation is also recognized as having a significant positive influence on employee performance. Keywords: work environment, job satisfaction, work motivation, employee performance